2007
DOI: 10.1021/jp0671188
|View full text |Cite
|
Sign up to set email alerts
|

The Dielectric Response of Room-Temperature Ionic Liquids:  Effect of Cation Variation

Abstract: In continuation of recent work on the dielectric response of imidazolium-based ionic liquids (ILs) (J. Phys. Chem. B, 2006, 110, 12682), we report on the effect of cation variation on the frequency-dependent dielectric permittivity up to 20 GHz of ionic liquids. The salts are comprised of pyrrolidinium, pyridinium, tetraalkylammonium, and triethylsulfonium cations combined with the bis-((trifluoromethyl)sulfonyl)imide anion. The dielectric spectra resemble those observed for imidazolium salts with the same ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
191
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 197 publications
(211 citation statements)
references
References 42 publications
17
191
1
2
Order By: Relevance
“…[13][14][15] However, Hunger et al have demonstrated that an Onsager-type equation adequately characterizes the temperature dependence of the static dielectric constant for a variety of ionic liquids. 10 Additionally, it is well-known that Onsager's equation is only applicable to aprotic liquids 16 and controversy exists about whether the imidazolium cation undergoes hydrogen bonding interactions.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] However, Hunger et al have demonstrated that an Onsager-type equation adequately characterizes the temperature dependence of the static dielectric constant for a variety of ionic liquids. 10 Additionally, it is well-known that Onsager's equation is only applicable to aprotic liquids 16 and controversy exists about whether the imidazolium cation undergoes hydrogen bonding interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The problem involved in ordering effect of the field energy and the disordering influence of thermal energy is such that each molecule with a permanent dipole moment µ makes a contribution to the polarization proportional to the field. [4]. However, Langevin idea that said that the dipole must be aligned completely in order to achieve saturation value failed to consider dipole-dipole interaction [5] (i.e., he neglected Eµ) and hence the expression he obtained for polarization cannot be used without modification when such an interaction in magnetic field is significant especially as it is caused by induced dipoles, which gives rise to dispersions.…”
Section: Introductionmentioning
confidence: 99%
“…Raman and optical Kerr-effect (OKE) spectroscopy have been able to access the relatively high frequency region from ~0.1 to 10 THz. [26][27][28] The sub-THz region, corresponding to intermolecular modes, has been investigated by terahertz time-domain spectroscopy [29,30], dielectric relaxation spectroscopy (DRS) [31][32][33][34][35][36][37], and OKE spectroscopy [3,5,26,[38][39][40][41][42][43][44][45]. In general, DRS is limited to a maximum frequency of about 100 GHz whereas the spectra of most RTILs are continuous up to several THz.…”
Section: Introductionmentioning
confidence: 99%